alternative RP‐HPLC method for the separation and determination of tocopherol and tocotrienol homologues as butter authenticity markers: A comparative study between two European countries - Górnaś, Paweł; Siger, Aleksander; Czubinski, Jaroslaw; Dwiecki, Krzysztof; Segliņa, Dalija; Nogala‐Kalucka, Malgorzata (European journal of lipid science and technology, 2014)
Eight tocochromanols (α, β, γ, and δ homologues of tocopherol and tocotrienol) naturally occurring in foods were successfully separated within a 13‐min run in the RP‐HPLC mode. Analytes were separated on the Phenomenex Luna PFP column filled with the pentafluorophenyl stationary phase (3 µm, 150 mm × 4.6 mm) using the mobile phase containing methanol:water (93:7 v/v) with an elution flow rate of 1 ml/min and column oven temperature of 40°C. The method was rapid, linear, accurate, and precise with detection limits in the range of 0.000184–0.000605 µg, preventing analyte losses due direct dissolution in 2‐propanol. The developed RP‐HPLC method in comparison with the NP‐HPLC mode had a significantly higher sensitivity, speed, and repeatability, but primarily it protected against the loss of analytes and thus reduced the risk of possible error measurements. It was found that tocopherol contents in the tested butter samples amounted to 2.00–16.92 mg/100 g for samples coming from Poland and 2.61–2.98 mg/100 g for samples from Latvia, respectively. The method is characterized by simplicity of implementation and it was successfully applied in the determination of tocochromanols in butter to verify product authenticity. Practical applications: To ensure consumers' protection, food products should be subject to continuous quality and authenticity control. One way to determine butter authenticity is to analyze native tocochromanol contents. This paper describes a simple and fast method determine plant oils added to milk fat with the use of RP‐HPLC techniques. Eight tocochromanols (α, β, γ, and δ homologues of tocopherol and tocotrienol) naturally occurring in foods were successfully separated within by RP‐HPLC. The method is rapid, linear, accurate, and precise with detection limits in the range of 0.184–0.605 μg. The method was successfully applied to determine tocochromanols in butter to verify product authenticity.